The effect of public transportation on the sustainability of Lebanon’s tourism industry - Ladki, Said (2016)
The purpose of this study is to investigate the effects of Lebanese public transport on the sustainability of internal and inbound tourism. The study dependent variables were the three research hypotheses: (1) safety of public transport; (2) reliability of public transport; and (3) fixed pricing. The results of the multivariate analysis test showed strong significance for the need to avoid stress and use the hop-on hop-off bus (F = 7.47, p = 0.001), the need for a reliable bus (F = 8.16, p = 0.01) especially for those living far from their work/school, and the need to save time on the road using the bus (F = 5.10, p = 0.012). Also, the study shows that those living far from their work/school (F = 5.15, p = 0.01) would prefer a monthly payment pass.